2018
DOI: 10.3390/su10124563
|View full text |Cite
|
Sign up to set email alerts
|

A Crowdsourcing Approach for Sustainable Last Mile Delivery

Abstract: Sustainable transportation is one of the major concerns in cities. This concern involves all type of movements motivated by different goals (mobility of citizens, transportation of goods and parcels, etc.). The main goal of this work is to provide an intelligent approach for Sustainable Last Mile Delivery, by reducing (or even deleting) the need of dedicated logistic moves (by cars, and/or trucks). The method attempts to reduce the number of movements originated by the parcels delivery by taking advantage of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 32 publications
0
36
0
3
Order By: Relevance
“…In [40], a new approach to the LMD problem which considers a crowdsourcing solution was presented. This solution is based on an open fleet of temporary transporters who do not take a specific route to deliver each package from the customer's pickup point to the final destination, but on the contrary, they make use of their usual routes in order to carry a package, either to its final destination or to a point where another transporter can pick it up and continue with the delivery process.…”
Section: Case Study: Voluntary Distribution Of Essential Goodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In [40], a new approach to the LMD problem which considers a crowdsourcing solution was presented. This solution is based on an open fleet of temporary transporters who do not take a specific route to deliver each package from the customer's pickup point to the final destination, but on the contrary, they make use of their usual routes in order to carry a package, either to its final destination or to a point where another transporter can pick it up and continue with the delivery process.…”
Section: Case Study: Voluntary Distribution Of Essential Goodsmentioning
confidence: 99%
“…Once the users register in the application by using their mobile devices, the system will be able to locate them in real time, and to share their current location to other users when necessary. From that moment on, whenever a customer issues a delivery request, a dynamic network analysis (explained in [40]) uses the fleet of geo-localized volunteers in order to calculate a particular path for delivering the goods to the customer's location. It is important to note that, in order to optimize each delivery, the system builds the complete delivery path as a chain of collaborative deliverers (the volunteers) in which each volunteer carries the package over some part of the path (a sub-path) and then passes it to the next volunteer.…”
Section: Case Study: Voluntary Distribution Of Essential Goodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stieger et al found in their research on the design of crowdsourcing incentive mechanisms that the key to motivating employees to complete crowdsourcing tasks is to create a suitable process incentive to guide users to participate [15]. Giret, aiming at the quality assessment of crowdsourcing results, proposed that the results could be evaluated from the four dimensions of novelty, flexibility, relevance and comprehensiveness [1].…”
Section: A the Mode And Mechanism Of Crowdsourcingmentioning
confidence: 99%
“…In the logistics industry, crowdsourcing provides a new idea for the sustainable development of logistics enterprises, and reasonable distribution pricing is the key to the sustainable development of logistics enterprises [1]. Therefore, this paper attempts to establish an optimal pricing model for logistics crowdsourcing tasks.…”
Section: Introductionmentioning
confidence: 99%